Exploring the Diversity and Regulation of Apocarotenoid Metabolic Pathways in Plants - Zheng, Xiongjie; Yang, Yu; Al-Babili, Salim (Frontiers in Plant Science, 2021)
In plants, carotenoids are subjected to enzyme-catalyzed oxidative cleavage reactions as well as to non-enzymatic degradation processes, which produce various carbonyl products called apocarotenoids. These conversions control carotenoid content in different tissues and give rise to apocarotenoid hormones and signaling molecules, which play important roles in plant growth and development, response to environmental stimuli, and in interactions with surrounding organisms. In addition, carotenoid cleavage gives rise to apocarotenoid pigments or volatiles that contribute to the color and flavor of many flowers and several fruits. Some apocarotenoid pigments, such as crocins and bixin, are widely utilized as colorants and additives in food and cosmetic industries, and also have health promoting properties. Considering the importance of this class of metabolites, investigation of apocarotenoid diversity and regulation has increasingly attracted the attention of plant biologists. Here, we provide an update on plant apocarotenoid biosynthesis pathway, especially highlighting the diversity of the enzyme carotenoid cleavage dioxygenase 4 (CCD4) from different plant species with respect to substrate specificity and regioselectivity which contribute to the formation of diverse apocarotenoid volatiles and pigments. In addition, we summarize the regulation of apocarotenoid metabolic pathway at transcriptional, post-translational and epigenetic levels. Finally, we describe inter- and intraspecies variation in apocarotenoid production observed in many important horticulture crops, and depict recent progress in elucidating the genetic basis of the natural variation in the composition and amount of apocarotenoids. We propose that the illustration of biochemical, genetic and evolutionary background of apocarotenoid diversity would not only accelerate the discovery of unknown biosynthetic and regulatory genes of bioactive apocarotenoids but also enable the identification of genetic variation of causal genes for marker-assisted improvement of aroma and color of fruits and vegetables and CRISPR-based next generation metabolic engineering of high-value apocarotenoids.